Demographic and work-related factors associated with burnout, resilience, and quality of life among healthcare workers during the COVID-19 pandemic: A cross sectional study from Malaysia - Marzo, Roy Rillera; ElSherif, Mohamed; Abdullah, Muhd Siv Azhar Merican Bin; Thew, Hui Zhu; Chong, Collins; Soh, Shean Yih; Siau, Ching Sin; Chauhan, Shekhar; Lin, Yulan (Frontiers in Public Health, 2022)
Introduction The healthcare setting is a stressful and demanding work environment, and healthcare workers face a continuous expansion of their job roles and responsibilities. Past studies have shown that factors affecting burnout, resilience, and quality of life among healthcare workers merit further research, as there were inconsistent findings, especially with regards to the influence of demographic and work-related factors. Therefore, this study aims to determine whether demographic and work-related factors are associated with burnout, resilience, and quality of life among healthcare workers. Method This cross-sectional study was conducted between February 15, 2022 and March 15, 2022, among 394 healthcare workers from Putrajaya and Selangor hospitals, Malaysia. Maslach Burnout Inventory, World Health Organization Quality of Life-BREF 26 inventory, and Brief Resilience Scale were utilized to capture information on burnout, quality of life, and resilience, respectively. Results The mean score of physical health of participants who work more than 10 h (11.38) is lower than participants who work from 8 to 10 h (13.00) and participants who work 7 h daily (13.03), p-value < 0.001. Similarly, the mean score of psychological health of participants who work more than 10 h (12.35) is lower than participants who work from 8 to 10 h (13.72) and participants who work 7 h daily (13.68), p-value = 0.001. Higher income levels were associated with high resilience and quality of life. Conclusion It is imperative that healthcare practitioners and policy makers adopt and implement interventions to promote a healthy workplace environment, address ethical concerns, and prevent burnout among healthcare workers during the COVID-19 pandemic. Managing the issue of long working hours could possibly result in improved resilience, burnout, and quality of life among healthcare workers. Despite this study able to tickle out some policy specific areas where interventions are needed, identifying effective solutions and evaluating their efficiency will require larger and interventional studies.